Pelatihan & Pemasaran Olahan Abon Ikan Tongkol Berbasis Digital Marketing Terhadap UMKM di Desa Pelangan - Sami’un; Astrid Octavia Bahari; I Ketut Kusuma Wijaya; Ahmad Fatoni Karim Amirullah; Septia Andriani (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This research aims to develop the capacity of Micro, Small and Medium Enterprises (MSMEs) in Pelangan Village through training and marketing of processed tuna fish meat products based on digital marketing. MSMEs in this village have great potential in developing local products, but face challenges in limited marketing and less than optimal use of digital technology. Therefore, this training is focused on improving the skills of MSME players in managing their business effectively by utilizing digital platforms such as social media, websites and e-commerce to market shredded tuna products. The method used in this research is a training and mentoring approach involving digital marketing theory and practice. It is hoped that the results of this research can increase MSME players' understanding of the importance of digital marketing and have a positive impact on increasing sales and visibility of processed tuna products in the wider market. It is hoped that effective digital marketing implementation will expand the marketing network, increase product competitiveness, and encourage local economic growth in Pelangan Village.